2019
DOI: 10.1200/jco.2019.37.7_suppl.201
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-free survival as a predictor of overall survival in non-metastatic castration-resistant prostate cancer.

Abstract: 201 Background: Recent trials have shown that apalutamide and enzalutamide can improve metastasis free survival (MFS) in advanced non-metastatic (M0) castrate-resistant prostate cancer (CRPC). MFS is a novel clinical endpoint, demonstrated to be a strong predictor of overall survival (OS) for localized prostate cancer, yet it is unknown if this is also true for M0 CRPC. Our aim was to determine how strongly MFS in M0 CRPC correlates with OS in a real world population. Secondary analyses evaluated whether a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…33 OS was ultimately selected because it was more clinically meaningful for patients who had difficulties drawing inference that MFS was a strong surrogate or predictor of OS as demonstrated in several analyses. 34,35 Furthermore, although MFS was used as an endpoint in trials, the definition varied. We also observed in our qualitative interviews that patients, caregivers, and physicians, all viewed OS as the most important efficacy attribute.…”
Section: Survey Developmentmentioning
confidence: 99%
“…33 OS was ultimately selected because it was more clinically meaningful for patients who had difficulties drawing inference that MFS was a strong surrogate or predictor of OS as demonstrated in several analyses. 34,35 Furthermore, although MFS was used as an endpoint in trials, the definition varied. We also observed in our qualitative interviews that patients, caregivers, and physicians, all viewed OS as the most important efficacy attribute.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Although the results of this analysis demonstrate a correlation between MFS and OS that is moderate to strong, accumulation of additional data can further strengthen these findings. This is demonstrated in the research conducted in Canada that reports strong correlation between MFS and OS with longer follow-up of the patients 24 . When MFS and OS events have further accumulated, the results from subgroup analysis as by PSADT at the index date may provide stronger insights.…”
Section: Discussionmentioning
confidence: 84%
“…Recent publications further support the redirection of the research and development focus on MFS as an accurate evaluative measure for cancer therapies. Of significance is the correlation of MFS with the overall survival (OS) of patients with nmCRPC [7]. It has recently been shown that metastasis development is associated with a significantly greater risk of death in men with high-risk nmCRPC; hence, MFS is predictive of OS [7].…”
mentioning
confidence: 99%
“…Of significance is the correlation of MFS with the overall survival (OS) of patients with nmCRPC [7]. It has recently been shown that metastasis development is associated with a significantly greater risk of death in men with high-risk nmCRPC; hence, MFS is predictive of OS [7]. When using MFS instead of OS as a clinical trial endpoint, investigators and clinicians will be able to observe the prognostic criteria earlier, allowing a more rapid evaluation of new anti-metastasis therapies.…”
mentioning
confidence: 99%